The prevalence and burden of musculoskeletal disorders amongst Indigenous people in Pimicikamak, northern Manitoba, Canada: A community health survey - André Bussières; Melissa Atkinson-Graham; Jennifer Ward; Muriel Scott; Jean Moss; Patricia Tavares; Deborah Kopansky-Giles; Jacqueline Ladwig; Cheryl Glazebrook; David A. Monias; Helga Hamilton; Donald Z. Mckay; et al. (Preventive Medicine Reports)
Objectives: To investigate the prevalence of spine symptoms and spine disability, self-care and care seeking behaviors in a random sample of Indigenous adults residing in Cross Lake, northern Manitoba, Canada. Study design and setting: Orally administered survey in Cree or English to a representative sample of Pimicikamak citizens from the treaty (n = 150/1931 houses) and non-treaty (n = 20/92 houses) land, between May and July 2023. Questions (n = 154) were derived from the 2018 First Nations Regional Health Survey, 2020 Canadian Community Health Survey, and 2021 The Global Burden of Disease study, covering demographics, spine symptoms, chronic conditions, activity limitations, general health, self-care, medication, and satisfaction with care. We used descriptive and cross-tabulations and consulted the community for data interpretation. Results: The survey was completed by 130 adults (65 % females, mean age, 48.4 years). Nearly all participants (89.6 %) reported having spine symptoms in the past four weeks, with a majority experiencing activity limitations lasting one day or more due to neck (77.9 %) or low back pain (55.6 %). Chronic neck and low back pain “sometimes or often” limited activities of daily living (52.8 % and 74.1 % respectively). Nearly two-third (65.4 %) did not have concomitant mood problems. Future preferred care included self-care (88.5 %), over-the- counter medication (64.6 %), seeing an allied care provider (45.4 %), a traditional healer (26.2 %), a nurse or a medical doctor (22.3 %). Conclusion: Spine symptoms were highly prevalent and significantly impacted activities of daily living. Nearly half of respondents felt that they could benefit from care provided by allied health providers.